Ancient duplicated conserved noncoding elements in vertebrates: A genomic and functional analysis - McEwen, Gayle K.; Woolfe, Adam; Goode, Debbie; Vavouri, Tanya; Callaway, Heather; Elgar, Greg

(untitled) (Genome Research, 2006)
Fish–mammal genomic comparisons have proved powerful in identifying conserved noncoding elements likely to be cis-regulatory in nature, and the majority of those tested in vivo have been shown to act as tissue-specific enhancers associated with genes involved in transcriptional regulation of development. Although most of these elements share little sequence identity to each other, a small number are remarkably similar and appear to be the product of duplication events. Here, we searched for duplicated conserved noncoding elements in the human genome, using comparisons with Fugu to select putative cis-regulatory sequences. We identified 124 families of duplicated elements, each containing between two and five members, that are highly conserved within and between vertebrate genomes. In 74% of cases, we were able to assign a specific set of paralogous genes with annotation relating to transcriptional regulation and/or development to each family, thus removing much of the ambiguity in identifying associated genes. We find that duplicate elements have the potential to up-regulate reporter gene expression in a tissue-specific manner and that expression domains often overlap, but are not necessarily identical, between family members. Over two thirds of the families are conserved in duplicate in fish and appear to predate the large-scale duplication events thought to have occurred at the origin of vertebrates. We propose a model whereby gene duplication and the evolution of cis-regulatory elements can be considered in the context of increased morphological diversity and the emergence of the modern vertebrate body plan.